2002
DOI: 10.1007/s00244-001-0032-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological Responses of Lumbriculus variegatus Exposed to Fluoranthene-Spiked Sediment

Abstract: Abstract. Lumbriculus variegatus was used as a bioassay organism to examine the impact of the sediment-associated polycyclic aromatic hydrocarbon (PAH) fluoranthene on behavior, reproduction, and toxicokinetics. The number of worms increased between the beginning and end of the experiment at 59 g g Ϫ1 fluoranthene, but at the next higher treatment (108 g g Ϫ1 ) the number of worms found was lower and not different from the control. Worms exposed to 95 g g Ϫ1 also exhibited increased reproduction when fed a yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…L. variegatus motion was highly heterogeneous. Although this organism is commonly described as an upward conveyor, , we observed several distinct behaviors, including sediment excavation, particle ingestion/egestion, rapid reworking of interfacial sediments, and deep burrowing. Burrows were biased to the upper 10 mm of the bed (99.6% of events), which left extensive areas of the subsurface unaltered (Figure a).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…L. variegatus motion was highly heterogeneous. Although this organism is commonly described as an upward conveyor, , we observed several distinct behaviors, including sediment excavation, particle ingestion/egestion, rapid reworking of interfacial sediments, and deep burrowing. Burrows were biased to the upper 10 mm of the bed (99.6% of events), which left extensive areas of the subsurface unaltered (Figure a).…”
Section: Discussionmentioning
confidence: 90%
“…We added 0.250 g of L. variegatus (Aquatic Research Organisms, Hampton, NH, United States) evenly over the SWI immediately following sediment stabilization. This corresponds to an organism density of 6300/m 2 , 37 which falls within the typical range of oligochaete densities in freshwater sediments (1000−40000/m 2 ). 38−40 L. variegatus egested and excreted the organic-rich test sediments, and no exogenous food was added during the experiment.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…However, we found no evidence to this effect in our study for these two microquantity approaches; we also did not find that the ability to estimate lipids between methods differed among species of varying lipid content or between tissue types (somatic vs. gonadal). Landrum et al (2002) also demonstrated that the microcolorimetric SPV and microgravimetric methods produce comparable results for aquatic algae. Additionally, measurement precision did not differ between microquantity methods in this study, regardless of species or tissue type analyzed.…”
Section: Microcolorimetric Spv Methods Vs Microgravimetric Methodsmentioning
confidence: 82%
“…Because microgravimetric analysis is more time-and labor-intensive than microcolorimetric SPV analysis (Landrum et al 2002(Landrum et al , 2004Inouye and Lotufo 2006), it was conducted only on samples collected during 2005. These samples included yellow perch, walleye, and walleye gonads (Table 1).…”
Section: Microgravimetric Analysismentioning
confidence: 99%
See 1 more Smart Citation